AWARENESS AND ATTITUDES OF CONSUMERS IN USING INTERNET FOR ONLINE PURCHASE - Laxmi, R.Anantha; Kumar, ArunSarath (International Journal of Research -GRANTHAALAYAH, 2016)
Online shopping behavior (also called online buying behavior and Internet shopping or buying behavior) refers to the process of purchasing products or services via the Internet. E-commerce has been growing very fast because of many advantages associated with buying on internet because of lower transaction and search cost as compared to other types of shopping. Through online shopping consumers can buy faster, more alternatives and can order product and services with comparative lowest price. Therefore, in this paper, the researchers have carefully analyzed the consumers’ attitude and behavior towards online shopping. This paper gives a comprehensive picture of the awareness and attitudes of consumersin using internet for online purchase. A sample size of one hundred and five respondents is selected for the research from Thoothukudi district. The study quantitatively analyses the awareness of consumers in using internet, attitudes and behaviors of the consumers in buying various products from internet, hours of using the internet and the like using primary data. Appropriate findings and suggestions are given in the paper.